Pengelolaan Sampah Terpadu di Desa Kuwum: Studi Kasus Banjar Balangan dan Balangan Kangin - Anak Agung Gede Agung Indra Prathama Prathama (Jurnal Pengabdian Kepada Masyarakat, 2025)
The waste management program in Desa Kuwum, specifically in Banjar Balangan and Balangan Kangin, addressed the community’s limited awareness and lack of infrastructure for waste segregation. Activities included socialization, education, training, and the distribution of waste segregation tools. Residents were introduced to Teba Modern for organic waste processing and Ecobricks for handling plastic waste. The program employed a participatory approach, encouraging active involvement from households. Initial results showed improved awareness and gradual adoption of waste segregation practices. Organic waste management and Ecobricks production demonstrated promising outcomes in fostering sustainable waste practices. This initiative highlights the importance of education, local resource utilization, and community engagement in advancing sustainable waste management efforts in rural settings.